Nanoparticles Enhanced Laser Induced Breakdown Spectroscopy of Gemstone - Suhaimi, Intan Husna; Haider Rizvi, Syed Zuhaib (Enhanced Knowledge in Sciences and Technology, 2023)
Abstract: A nanoparticle is a tiny particle that scales in size from 1 to 100 nanometers, which are invisible to the naked eye, can have significantly different physical and chemical properties than their larger material counterparts. With the revolution of industries worldwide, nanoparticles have been widely used across variety of industries sector, pharmaceutical purposes, cosmetics, and environmental preservation. Laser Induced Breakdown Spectroscopy (LIBS) is a persuasive elemental analysis method. This study will applied the high energetic laser pulse using Nd:YAG laser of 1064nm and HR4000 spectrometer to determine the mineral composition in gemstones spectroscopically. Spectral lines observation in this LIBS spectrum will be used to identify the heavy metal elements. The laser-induced breakdown spectroscopy clarifies the existence of organic and non-organic elements for instance Ca, Si, Al, C and other materials in gemstones. LIBS can be very significant tool in analyzing and obtain the chemical composition and validate the presence of various materials identified in LIBS spectral lines of gemstones when covered with nanoparticles.